Multilevel bivariate analysis of the association between high-risk fertility behaviors of birth and stunting with associated risk factors in Ethiopia - Fenta, Wondaya; Zeru, Melkamu A. (Frontiers in Nutrition, 2024)
Currently, the linkage between high-risk fertility behavior of birth and stunting among under five children continues as a public health problem in developing countries, including Ethiopia. This issue poses a threat to the health and overall well-being of children. Thus, the main objective of this study was to examine the association between high-risk fertility behavior of birth and stunting status of children. Method: The data used for this study was extracted from the recent Ethiopian Mini Demographic and Health Survey data 2019. A total weighted sample of 4969 under five children were included in this study and the relevant data was extracted from those samples. The multilevel bivariate analysis was used to assess the association between high-risk fertility behavior of birth and the stunting status of under-five children in Ethiopia. Results: Among 4997 under-five children in the study, 24% of under-five children were experienced stunting as a result of high-risk fertility behavior of birth. Our study also revealed that, an intra-class correlation of 0.2, indicating that 20% of the variability in both high-risk fertility behaviors of birth and stunting can be attributed to differences between communities. Furthermore, there was a statistically significant association between high-risk fertility behavior of birth and the stunting status of children under the age of five [AOR = 8.5, 95% CI: (5.58, 18.70)]. Similarly, the stunting status of birth among males were 1.36 times greater than to the estimated odds of stunting status of birth among females [AOR = 1.36, 95% CI :( 1.19, 1.55)]. Conclusions: This study found that, there was a significant statistical association between high-risk fertility behavior of birth and stunting status of under five children. Specifically, children born to mothers under 18 years and in households with high parity were identified as the main risk factors for child stunting. Furthermore, health-related education, improved access to maternal healthcare, and training interventions were associated with high-risk fertility behavior during birth and child stunting. The study suggests that regular health assessments and early interventions for infants born to mothers with high-risk reproductive characteristics are crucial to reducing the impact of child stunting under five age.